The Effects of the Noise and Reverberation on the Working Memory Span of Children - JIANXIN, Peng; PENG, Jiang (Archives of Acoustics, 2018)
Three different reverberation time (RT) conditions were obtained by room acoustical simulation. The working memory span of grades 3 (8 to 9 years old) and 6 children (11 to 12 years old) was tested under these reverberation conditions with different signal-to-noise ratio (SNR) by headphone reproduction in a quiet classroom. The working memory span scores (WMSSs) were obtained under the different RTs and SNRs conditions. The results demonstrated that children’s age, RT and SNR had significant effect on children’s WMSSs. With the increase of SNR and the decrease of RT, the WMSSs increased gradually. Under the same SNR and RT condition, the children’s WMSSs were increased with the increase of their age. Multiple linear regression analysis shows that children’s WMSSs are related to age, RT and SNR, and the correlation coefficient is 0.99.